Theoretical local buckling and bulging analysis on miniature buckling-restrained brace with corrugated core bar. (February 2023) - Gu, Tianyu; Liu, Yan; Jia, Liang-Jiu; Ge, Hanbin
Abstract: An all-steel miniature buckling-restrained brace with corrugated core bar, termed as CMBRB, which consists of a metallic core bar with smooth notches and a circular restraining tube, was proposed, and it is proved to have enhanced ductility and stable hysteretic behaviors under seismic events. In this study, 12 specimens were tested under cyclic loading to investigate effects of slenderness ratio, segment spacing-to-notched cross section height ratio and Teflon spacers on mechanical behaviors of CMBRBs, and the first 2 parameters were found to have great effects on strength, stiffness, energy dissipation and ductility, while the spacers contribute no significant effect. 3 different buckling cases were defined for CMBRBs with different core bar geometries, and corresponding theoretical buckling analyses were conducted to obtain lateral thrust generated by contact between core bar and restraining tube. The proposed buckling models have high accuracy as the relative error between theoretical and numerical results is only 3.9%, and it was found that CMBRBs are more susceptible to local bulging failure than conventional miniature buckling-restrained braces. Finally, a simple design procedure was developed to prevent local bulging failure of CMBRB, and the proposed design criterion showed good agreement with both experimental and numerical results in this study with a safety factor of 1.13. Highlights: Experimental study on mechanical performance of miniature buckling-restrained brace with corrugated core bar (CMBRB) conducted. Analytical models for predicting lateral thrust caused by local buckling of CMBRB proposed. Numerical analysis to validate the proposed analytical models conducted. A simple and conservative design criterion to prevent local bulging of CMBRB proposed. A step-by-step design procedure for premature bulging failure prevention of CMBRB proposed.